Useful valuable plants of Maithili community in Eastern Nepal: An ethnobotanical study - Mallik, Anand Raj; Chaudhary, Sujan; Shrestha, Sabitri (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(2): 439-446, 2020 (December)